Applicability of Graphene Oxide Interlayers in PEMs for Reducing Crossover in Electrochemical Acetone Hydrogenation Reactors - Komma, Miriam; Marth, Axel; Maier, Maximilian; Hutzler, Andreas; Böhm, Thomas; Thiele, Simon (Journal of The Electrochemical Society, 2024)
Highlights GO interlayers in PEMs to reduce the crossover in acetone hydrogenation reactors. Crossover was significantly reduced by the GO composite membrane. Blocking effect of the GO interlayer was accompanied by an increased OCV. Crossover reduction scales with increasing GO loading in the PEM. Blocking effect was maintained after running experiments at demanding conditions.
CRIS-Team Scopus Importer:2024-10-25
Keywords: acetone hydrogenation; acetone hydrogenation reactor; crossover reduction; electrochemical acetone reduction; graphene oxide